THE INFLUENCE OF PROBLEM BASED LEARNING AND MIND MAPPING MODELS ON LEARNING OUTCOMES INDONESIAN LANGUAGE STUDENTS OF CLASS X AT SMAN PAKUSARI - Chimayatul Aidah (Journal of Education Technology and Inovation, 2022)
Learning needs to be emphasized on process and quality to realize maximum learning outcomes. Learning Indonesian in class X is still not getting optimal results, so there is a need for a new model to be implemented, namely by using a problem based learning model and a mind mapping model. Learning with this observation report material is appropriate to use the problem based learning model because students are directly involved with what they see. Meanwhile, the concept map model makes it easier for students to design texts.The purpose of this study was to determine: (1) there is an effect of the Problem Basic Learning (PBL) Model on Indonesian Language Learning Outcomes for Class X Students at SMAN Pakusari Jember Regency, (2) there is an influence of the Mind Mapping Model (MM) on Language Learning Outcomes. Indonesia Class X Students at SMAN Pakusari Jember Regency, and (3) Is there an effect of the Problem Basic Learning (PBL) Model with the MIND MAPPING (MM) Model on the Indonesian Language Learning Outcomes of Class X Students at SMAN Pakusari Jember Regency. This quantitative research method is experimental. Due to the large population, the sub- population of the study was taken as many as 35 students. The school is SMA Negeri Pakusari class X 1 which uses 2 models, namely the Problem Basic Learning Model (PBL) and the Mind Mapping Model (MM). The data analysis technique in this study is to use two-way analysis. Based on the hypothesis test, it is proven that: (1) there is an effect of the Problem Based Learning model on the Indonesian Language Learning Outcomes of Class X Students on the LHO learning outcomes in the comparison of learning outcomes before and after treatment, the tcount value is 33.4356 with a significance value of 0.110. Because the value of tcount > ttable or the significance value is smaller than the 5% significance level. (2) There is an effect of the Mind Mapping model on Indonesian Language Learning Outcomes of Class X Students on learning outcomes in the comparison of Learning Outcomes before and after treatment, the tcount value is 32.569 with a significance value of .000 Because the tcount > ttable or the significance value is more smaller than the 5% level of significance. (3) There is an Influence of Problem Based Learning Model and Mind Mapping Model Together on Learning Outcomes for class X LHO in comparison of learning outcomes before and after treatment, the tcount value is 6.377 with a significance value of 0.206. Because the value of tcount > ttable or the significance value is smaller than the 5% significance level